Pelatihan Pemanfaatan Sampah Organik sebagai Upaya Menumbuhkan Gerakan Peduli Lingkungan - Joko Setiyono; Masnuatul Hawa; Sutrimah Sutrimah; M Alfin Fathoni (IKIP PGRI Bojonegoro, 2023)
MI Mambaul Huda Ngraseh is a private school located in Ngraseh Village, Dander District, Bojonegoro Regency. This school is located approximately 100 meters from the village market Ngraseh MI mambaul Huda has a large number of students, approximately in grades 1-6 there are 400 students. The number of students, of course, also makes the trash in the school environment also more and more. Therefore, this study aims to: (1) disseminate information about the types of organic and non-organic waste; (2) instill awareness and care for a clean environment to the students; and (3) conduct training that supports the use of organic waste for composting. The research method used are presentation and practice. The subjects of this study were 30 students of MI Mambaul Huda Ngraseh, consisting of 15 male students and 15 female students. The results of study showed that the enthusiasm of MI Mambaul Huda students was high. This can be seen through the results of student responses in questionnaire to the training on the use of organic waste, namely the satisfaction indicator for the topic material in which 20 students answered very interesting; for the clarity of material, there were 16 students answered very interesting; for the media, there were 15 students answered very interesting, and for the material practice indicators, there were 20 students answered very interesting. MI Mambaul Huda Ngraseh merupakan sekolahan swasta yang terletak di Desa Ngraseh Kecamatan Dander Kabupaten Bojonegoro. Sekolahan ini terletak kurang lebih 100 meter dari pasar desa Ngraseh MI mambaul Huda memiliki jumlah siswa yang banyak, kurang lebih kelas 1-6 ada sejumlah 400 siswa. Banyaknya mahasiswa tentunya juga membuat sampah yang ada dilingkungann sekolah juga semakin banyak. Oleh sebab itu penelitian ini bertujuan untuk: (1) melakukan sosialisasi tentang jenis sampah organik dan nonorganik; (2) menanamkan sikap sadar dan peduli lingkungan bersih pada siswa; dan (3) melakukan pelatihan yang mendukung pemanfaatan sampah organik untuk pembuatan pupuk kompos. Metode penelitian yang digunakan adalah metode presentasi dan praktik. Subyek penelitian ini adalah 30 siswa MI Mambaul Huda Ngraseh, yang terdiri dari 15 siswa laki-laki dan 15 siswa perempuan. Hasil penelitian meunjukkan antusiasme siswa MI Mambaul Huda yang tinggi hal ini dapat dilihat melalui hasil angket respon siswa terhadap pelatihan pemanfaatan sampah organik, yaitu indikator kepuasan topik materi 20 siwa menjawab sangat menarik, kejelasan materi 16 siswa menjawab sangat menarik, media 15 siswa menjawab sangat menarik, dan pada indikator praktik materi 20 siswa menjawab sangat menarik.